Desentralisasi Fiskal terhadap Pembangunan Ekonomi di Daerah - Ahmad Heri Widodo; Agus Eko Sujianto; Subhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate the impact of fiscal decentralization on economic development at the regional level in Indonesia. Employing a quantitative approach, secondary data and surveys were utilized to examine the relationships among fiscal decentralization variables, financial transfers, fiscal autonomy, and economic growth. The analysis results reveal that fiscal decentralization has a significant positive impact on regional economic growth, with levels of fiscal autonomy and the magnitude of financial transfers from the central government emerging as critical factors in enhancing local economic performance.